Lacanism and retorics in two expressions of the Real in peruvian poetry from the politic violence years: Alejandro Romualdo y Pablo Guevara - Arámbulo López, Carlos Manuel (2018)
This study approaches two books of poems dealing with the disappeared during the terror years in Perú (1980-1990), "A los ataúdes, a los ataúdes" from Pablo Guevara (1999) and "Ni pan ni circo" from Alejandro Romualdo (2005). Both authors deal with an image on the Real following different approaches to the five components of clas- sic rhetoric and also to the "intellection" as symbolizing procedure for literary creation. The proposal intends to close the gap between lacanian texts psychoanalysis and General textual rhetoric following Stefano Arduini.